Co-culture of microalgae-activated sludge in sequencing batch photobioreactor systems: Effects of natural and artificial lighting on wastewater treatment. (January 2022) - Nguyen, Thi-Thuy-Duong; Bui, Xuan-Thanh; Nguyen, Thanh-Tin; Hao Ngo, Huu; Yi Andrew Lin, Kun; Lin, Chitsan; Le, Linh-Thy; Dang, Bao-Trong; Bui, Manh-Ha; Varjani, Sunita
Graphical abstract: Highlights: Effects of artificial and natural lighting on photobioreactors were investigated. COD removal of artificial lighting mode was 13.2% higher than that of natural one. Nutrients removal between two lighting conditions were not significantly different. Light intensity had strong positive correlation with biomass and DO concentration. Natural lighting saved 57% energy consumption compared with artificial lighting. Abstract: Co-culture using microalgae-activated sludge in Sequencing Batch Photobioreactors (PBRs) was investigated for wastewater treatment performance. This study evaluated the effect of natural and artificial lighting conditons on treatment performance under consideration of energy consumption. The results found that the removal of nutrients and COD of natural lighting condition was only 10% and 13% lower than those of artificial lighting respectively. Generally, artificial lighting mode took an advantage in pollutants removal. However, standing at 0.294 kWh L -1, the total energy consumption of natural lighting was over two times less than that of artificial lighting. It reveals the natural lighting system played a dominant role for cutting energy costs significantly compared to artificial lighting one (∼57%). As a practical viewpoint on energy aspect and treatment performance, a natural lighting PBR system would be a sustainable option for microalgae-activated sludge co-culture system treating wastewater.